FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI GULA DI PT. MADUBARU (MADUKISMO) YOGYAKARTA - Abdul Syafri; Ignatius Suprih Sudrajat (Fakultas Pertanian UST, 2018)
The research aims to find out the factors of sugar production in PT. Madubaru Yogyakarta with the title of factors that affect the production of sugar in PT. Madubaru Yogyakarta. Research conducted at PT. Madubaru Tirtonirmolo, Kasihan, Bantul, Daerah Istimewa Yogyakarta. Site selection is Purposive with the consideration that PT. Madubaru is the only Sugar and Alcohol / Spirtus factory that is tasked to succeed the national food procurement program, especially sugar in DIY. The method of analysis used is quantitative analysis. Quantitative analysis in this research use Cobb Douglas production function with Ordinary Least Square method to see the effect of predetermined variables on sugar production of PT. Madubaru. The result of F-test for all four factors together shows that all four factors together influence to sugar production in PT. Madubaru. Meanwhile, to test each factor of production by using t-test and t-table test criteria, only one factor of production has real effect on sugar production that is rendemen.. Based on the results of regression analysis with OLS estimation, it can be concluded, The test results together there are four factors of production that affect the level of real Î± = 0.05 to sugar production in PT. Madubaru. These factors, namely the amount of sugar cane and auxiliary materials, rendemen, total labor and machine hours. And partial test results obtained that the yield of real effect on sugar production in PT. Madubaru